2018
DOI: 10.1002/ana.25303
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer–N‐acetyl‐L‐cysteine modulates monophagocytic response in adrenoleukodystrophy

Abstract: ALD phenotypes display unique inflammatory profiles in response to VLCFA stimulation, and therefore ex vivo monophagocytic cells may provide a novel test bed for therapeutic agents. Based on our findings, D-NAC may be a viable therapeutic strategy for the treatment of cALD. Ann Neurol 2018;84:452-462.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 30 publications
(92 reference statements)
0
33
0
Order By: Relevance
“…Likewise, the 6MWT may be meaningful to monitor the clinical treatment efficacy. The observed tolerability, safety, and signs of clinical benefit of this pilot study may warrant the long-term use of these or other next-generation antioxidants [53] in a phase III, double-blind, randomized, placebocontrolled clinical trial with a larger number of subjects. The safety and tolerability of the doses used may facilitate extension of similar antioxidant combinations to other diseases that share both axonal degeneration as a significant component of clinical progression and redox imbalance as a primary or early contributing pathogenic factor [54,55].…”
Section: Discussionmentioning
confidence: 90%
“…Likewise, the 6MWT may be meaningful to monitor the clinical treatment efficacy. The observed tolerability, safety, and signs of clinical benefit of this pilot study may warrant the long-term use of these or other next-generation antioxidants [53] in a phase III, double-blind, randomized, placebocontrolled clinical trial with a larger number of subjects. The safety and tolerability of the doses used may facilitate extension of similar antioxidant combinations to other diseases that share both axonal degeneration as a significant component of clinical progression and redox imbalance as a primary or early contributing pathogenic factor [54,55].…”
Section: Discussionmentioning
confidence: 90%
“…As with most neurologic disease, main pharmacodynamic challenges are in passing the blood–brain barrier and in the targeted delivery of a therapeutic compound. Recently, a nanoparticle polyamidoamine, PAMAM, dendrimer drug delivery platform conjugated to NAC (D‐NAC), having shown rescue of motor impairments and inflammatory status in a neonatal rabbit model of cerebral palsy (Kannan et al, ), demonstrated targeted drug delivery into Abcd1 mouse spinal cord microglia, and in ex vivo cerebral ALD peripheral blood monocytic patient cells stimulated by VLCFA (C26:0), normalization of antioxidant and inflammatory status (Turk et al, ).…”
Section: Experimental Therapeutic Trials and Strategiesmentioning
confidence: 99%
“…VLCFA stimulation of CCALD patient macrophages results in a dramatic proinflammatory response of these cells along with reduction of antioxidant capacity. 28 In addition, disruption of oxidative phosphorylation has been shown to correlate with VLCFA dose increase in ABCD1 deficiency fibroblasts. 29,30 Impaired autophagy, 31 increase in endoplasmic reticulum stress 32 and impaired endothelial tight junction functions 33 have also been observed as a consequence of VLCFA increase in ABCD1 mutant cells.…”
Section: Discussionmentioning
confidence: 99%